Problems and strategies related to patient safety in primary health care (Research, Society and Development, 2020)
Objectives: To describe the main problems related to patient safety in Primary Health Care from the perspective of nurses; list change strategies that strengthen patient safety in Primary Health Care. Method: Descriptive research, with a quantitative and qualitative approach. In the quantitative one, the Medical Office Survey on Patient Safety Culture instrument was used and in the qualitative one, the causal chain model and the Organizational Development Theory were chosen. Data collection took place from July to December 2017, in 14 health units in a city in southern Brazil. 51 nurses participated. Results: Patient safety problems related to: equipment, exams, medical records, professional quantity, haste, work flow, service management, quantity being more important than quality, information exchange and to professionals who believe that mistakes can be used against you. In view of these, generic strategies were developed, related to the structure, such as equipment maintenance, acquisition of materials, increase of the staff and improvements in the computerized system; and specific, related to the management process, with actions aimed at improving the local work process. Conclusion: The description of the problems for patient safety in Primary Care makes it possible to list strategies aimed at strengthening the safety culture.